Iklim Organisasi di Dinas Pendidikan dan Kebudayaan Kabupaten Pasaman Barat - Susanti, Lusi; Lara maisiska; Sabandi, Ahmad; Ningrum, Tia Ayu (Global Action and Education for Society, 2023)
This study aims to obtain information about the organisational climate in the education office and West Pasaman district seen from indicators of warmth, innovation, cooperation, openness, support and responsibility in the West Pasaman District Education and Culture Office. This type of research is descriptive research. The research population was all employees at the West Pasaman Regency Education and Culture Office, totaling 72 people. Determination of the magnitude is determined by the Slovin formula, withdrawal using saturated sampling technique. The instrument used was a questionnaire with a Likert scale and tested its validity and reliability. Furthermore, the data collected is analysed by finding the average and categorising the level of achievement. The results showed that organisational climate was seen 1) warmth 4.3, 2) innovation 4.3, 3) collaboration 4.4, 4) openness 4.4 5) support 4.3 and 6) responsibility 4.3. So the organisational climate in the Pasaman Barat district education office is included in the conducive category with an average score of 4.4.